Bacillus thuringiensis and their endophytic capabilities - Sauka, Diego Hernan (2017)
The main characteristic of Bacillus thuringiensis is that during sporulation produces a parasporal inclusion formed by one or more proteinaceous bodies that exhibit insecticidal activity upon ingestion by susceptible larvae of different orders of insects. In addition, the crystals are composed of insecticidal proteins (Cry/Cyt) and constitute the active ingredient of the most widely used biological insecticide